Advanced Nursing Practice: International Experiences and Future Direction for Nursing in Slovenia, Book of Abstracts (University of Maribor Press, 2021)
First international Advanced Nursing Practice conference in Slovenia brought world leading academic scholars to exchange and share their experiences on Advance Nursing Practice (ANP) education and practice. Special emphasis will be put on presentation of competencies, roles and scope of practice. Aim of our conference was to bring ANP education and especially the nature of ANP practice closer to an academic and clinical environment as well to decision making bodies in government and other professional groups in Slovenia. Numerous studies have shown that advanced practice nurses can provide quality patient care by role extension or expansion, contribute to efficacy, cost efficiency, patient satisfaction, reduced (re)hospitalizations, and reduced mortality. Experts from countries where ANP is well established and experts from countries where ANP is in the beginning stages of development participated in round table discussion. Conclusions of the round table discussion produced future direction for development of ANP in Slovenia.